One User – Two Viewpoints? An Examination of Information Privacy Concerns from the Employee and Consumer Perspective - Marco Wall (Junior Management Science (JUMS), 2022)
This study aims to answer two questions about the investigation of privacy concerns in the use of video call applications: Firstly, it aims to find out how privacy concerns of users of these technologies differ in the work context from the private context. Secondly, this paper wants to discover the underlying cause for these differing concerns. To answer these questions, focus group interviews were conducted with users who use video call applications in both the business and personal contexts. The results of the qualitative research were presented visually using a thematic map. Users expressed great privacy concerns regarding the control of sensitive data. In addition, work behaviour and employment relationships are becoming more transparent, which raises more concerns. Employees in particular try to protect private, confidential data at work. This paper presents one of the first exploratory findings in the field of privacy research in the workplace.
Keywords: 650; Information privacy; privacy concerns; online privacy; video call applications; workplace privacy